The 'Daily Herald' Order of Industrial Heroism, 1923 (front) (1923)
1923 1918-1939 "The 'Daily Herald' Order of Industrial Heroism, 1923 (front)" [T0298.jpg], 1923 The 'Daily Herald' instituted the Order of Industrial Heroism in 1923 to recognise the deeds of valour' of those workers who had saved their fellow workers from danger or death and became known as the "Workers' V.C.". Many of the 440 awards were posthumous. After a peak of 5235 recorded deaths in 1912, the number of industrial accidents was in decline, but in 1923 there were still 3302 deaths, almost 1300 in coal mines alone.